PENERAPAN UNSUR PASAL 2 AYAT (1) UNDANG-UNDANG NOMOR 21 TAHUN 2007 TENTANG TINDAK PIDANA PERDAGANGAN ORANG PADA PENYIDIKAN DIUNIT PPA SATRESKRIM POLRES BUKITTINGGI - Rahmad Natun (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
The Bukittinggi Regional Police PPA Satreskrim Unit has received the Policereport No: LP / 07 / A / I / 2018 / SPKT / Res-Bkt, dated January 8, 2018, concerningcases suspected of being criminal acts of Trafficking in Persons. Where there has been asuspicion of a criminal offense